Narrative inquiries of school reform : storied lives, storied landscapes, storied metaphors - Craig, Cheryl J (Research in curriculum and instruction., 2003)
This book culminates five years of extensive field-based inquiry with teachers and principals in four reforming school contexts. It arises from living alongside teachers and principals, entering into their realities, engaging them in conversations, seeing school life through their eyes, and employing the words and images they use to wrap around their experiences. It involved thinking narratively about schools as sites of high drama within which teachers and principals negotiate meaning as knowledgeable and knowing human beings. It gave primacy to everyday events taking shape on school landscapes. It meant creating spaces and devoting enormous amounts of time to observing and listening hard to what teachers and principals say and do when reform initiatives become personally lived in context--from their points of view.